Linguacultural Aspects of Somatisms in English Russian and Uzbek Languages - Abduraimova Anora Norbo’tayevna (Genius Publishing Group, 2022)
This study is devoted to the importance of a comparative study of languages in order to identify their national and cultural specifics. The choice of somatic phraseological units for research is explained not only by their wide use in everyday life, but also by the fact that they are expressive, figurative, clearly reflect the peculiarities of the spiritual and material life of the people. The study of the mechanisms of the emergence and use of phraseological units with a component of somatism in English, Uzbek and Russian helps to identify the features of verbal thinking of native speakers, because It is in phraseology that the tangible objective and sensual-emotional world of a person is most clearly reflected
Keywords: Comparative Study; National And Cultural Specifics; Figurative Meaning; Material Life